Detailed Study of Sulfur Poisoning and Recovery of Ni-YSZ-Based Anodes Operating up to 1.8 W cm-2 in a Biogas Fuel. (16th February 2023) - Ma, Jianjun; Jiang, Yao; Connor, Paul A.; Gamble, Stephen R.; Cassidy, Mark; Jiang, Cairong; Irvine, John T. S.
Abstract : Ni-YSZ (nickel-yttrium-stabilized zirconia) is a common anode for solid oxide fuel cells (SOFCs) because of its excellent catalytic performance and electronic conductivity. It shows that the nickel anode-supported cell exhibits good cell performance in a biogas fuel of 36CH4 -36CO2 -20H2 O-4H2 -4CO. Unfortunately, natural biogas fuels often contain sulfur, so using nickel anodes is not always straightforward. This paper investigates the sulfur poisoning and the recovery of BaCe0.7 Zr0.1 Y0.1 Yb0.1 O3- δ - (BCZYYb-) (Ce, Y, and Yb codoped barium zirconate) impregnated nickel anode-supported cells operating up to 1.8 W cm -2 in the biogas. The in situ gas analysis reveals that the suppression of the reforming reactions might cause sulfur poisoning in a 4 ppm (v) H2 S (hydrogen sulfide) in open circuit conditions, whereas the current degradation in working conditions could be attributed to the deactivation of reforming reactions and catalyst activity. The incidence of water-gas shift reactions is associated with the degradation rate of these two reactions. After removing the H2 S, the recovery is accelerated by a steam hydrogen fuel, indicating that steam facilitates the efficient release of sulfur from nickel sites.